(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
Electronic textiles (E-textiles) have emerged as promising platforms for applications in healthcare, sports training, and human-machine interaction, owing to their flexibility, permeability and integration capability. Printing technologies such as inkjet, screen, stencil, gravure, and flexographic printing offer scalable and cost-effective routes for fabricating conductive pathways and embedding functional components onto textiles. Despite rapid progress, the development of high-performance printed E-textiles is hindered by challenges in ink formulation, printability, mechanical compatibility, and especially ink-textile adhesion. Current research lacks a systematic understanding of how ink properties influence long-term durability and device functionality under real-world use. This review aims to address these issues by discussing recent advances in functional inks for printed E-textiles, with a focus on ink composition, printing techniques, and adhesion strategies. Key insights into the relationship between material properties and textile performance are highlighted. Finally, future directions are proposed to guide the development of durable, stretchable, and reliable printed E-textiles.